PENGARUH STRUKTUR MODAL, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAAN MANUFAKTUR YANG TERDAFTAR DI BEI - azhar, iqlima (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to analyze the effect of Capital Structure, Liquidity and Company Size on the Financial Performance of Food & Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange. This study is a quantitative study with a population of food and beverage companies listed on the IDX for the 2017-2021 period, then purposive sampling was carried out to obtain 11 company samples. This study uses secondary data in the form of annual financial reports, which were analyzed using multiple linear regression methods t-test, f-test and coefficient of determination test through the SPSS version 25 application. The results show that Capital Structure has a significant effect on Financial Performance (p = 0.000), Liquidity has a significant effect on Financial Performance (p = 0.008) and Company Size has a significant effect on Financial Performance (p = 0.005), Simultaneously, the variables Capital Structure, Liquidity and Company Size have a significant effect on Financial Performance of food & beverage sub-sector manufacturing companies (p = 0.000), with a coefficient of determination of 56.1%. This shows that the independent variables can explain 56.1% of the variation in financial performance, while the remaining 43.9% is influenced by other factors outside this study.